International multicentre observational study to evaluate the association between perioperative red blood cell transfusions and 1-year mortality after major cancer surgery (ARCA-1): study design, statistical analysis plan and study protocol. Issue 3 (18th March 2021) - Cata, Juan; Ramirez, Maria; Forget, Patrice; Chen, Lee-Lynn; Diaz-Cambronero, Oscar; Chen, Wankun; Warner, Matthew A; Knopfelmacher Couchonal, Adriana; Pelosi, Paolo; Cuellar, Luis; Corrales, German; Romero, Carlos; et al.
Abstract : Introduction: Blood transfusion is still common in patients undergoing major cancer surgery. Blood transfusion can be associated with poor prognosis in patients with cancer. Perioperative Care in the Cancer Patient -1 (ARCA-1) aims to assess in a large cohort of patients the current incidence, pattern of practice and associations between perioperative blood transfusions and 1-year survival in patients undergoing major cancer surgery. Methods and analysis: ARCA-1 is a prospective international multicentre observational study that will include adult patients scheduled to have major cancer surgical procedures with the intention to cure, and an overnight planned hospital admission. The study will be opened for 1 year for enrolment (7 January 2020–7 February 2021). Each centre will enrol patients for 30 days. The primary endpoint of this study is all-cause mortality 1 year after major cancer surgery. Secondary endpoints are rate of perioperative blood product use, cancer-specific mortality at 1 year and PFSs and 30-day morbidity and mortality. Ethics and dissemination: This study was approved by the Institutional Review Board at The University of Texas—MD Anderson Cancer Center. The study results will be published in peer-reviewed journals and disseminated at international conferences. Trial registration number: NCT04491409 .